'Too late or too soon': The ethics of advance care planning in dementia setting. (6th December 2020) - Perin, Marta; Ghirotto, Luca; De Panfilis, Ludovica
Abstract: Advance care planning (ACP) is considered a pivotal aid in the decision‐making process, especially for many people living with dementia, who inevitably will lose the capacity to make decisions at the end of life. In Italy, ACP has been recently regulated by law 219/2017, leading to the investigation of how physicians deal with ACP in dementia. In order to comprehend the perception of physicians who provide care for patients with dementia regarding ACP and to describe their difficulties and needs, this study presents the results of a qualitative research study performed within a local health authority in northern Italy. Data were collected by semi‐structured interviews with 11 physicians dealing with patients with dementia and were analysed using interpretative phenomenological analysis. Four superordinate themes were identified, describing both the difficulties and challenges perceived by physicians in performing shared ACP in their daily activities. This study demonstrates that physicians experience troubles synchronizing the time of shared ACP with the more rapid development of dementia. Results also suggest that further training about communication on ACP is urgently required to ease the implementation of shared ACP. A broader involvement of institutions and other professionals is also important in spreading ACP among healthcare institutions.